A CLOSER LOOK AT GRIT AND LANGUAGE MINDSET AS PREDICTORS OF FOREIGN LANGUAGE ACHIEVEMENT - Khajavy, Gholam Hassan; MacIntyre, Peter D.; Hariri, Jamal (Studies in second language acquisition, 2021)
Learning a second/foreign language (L2) is a long process and L2 learners certainly will encounter setbacks and discouragements during this process. However, their reactions to these failures might be different based on their perceptions of L2 learning ability and their subsequent effort put into L2 learning. Based on this, the present study aimed at exploring two underresearched constructs within the field of applied linguistics, namely grit (continuous effort and interest for long-term goals) and language mindset (individuals’ perceptions of their language learning ability). We had five main aims: to examine (a) the factor structure of grit, (b) the factor structure of language mindset, (c) whether there are gender differences in grit or language mindset, (d) the relationships between language mindset and grittiness, and (e) the roles of grit and language mindset as predictors of L2 achievement. To address these aims, a total number of 1,178 university students who were taking general English courses took part in our study and completed the questionnaires. Results of confirmatory factor analysis indicated that the two-factor structure for both grit and language mindset fit the data better than the single-factor structure. We also tested several structural equation models and found that a growth language mindset weakly, but positively, predicted one component of grit (perseverance of effort, or POE), but not the other (consistency of interest, or COI). A fixed language mindset did not predict POE, but did negatively predict COI. Finally, only growth language mindset was a weak, positive predictor of L2 achievement. At the end, theoretical and pedagogical implications regarding the role of grit and language mindset in L2 learning are presented.